2016
DOI: 10.1111/hel.12340
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and extragastric diseases

Abstract: During the past year, many articles were published on the extragastric diseases related to Helicobacter pylori infection. This supports the theory that some microorganisms may cause diseases even far from the primary site of infection by interfering with different biologic processes. The role of H. pylori on idiopathic thrombocytopenic purpura, sideropenica anemia, and vitamin B12 deficiency is well known. On the other hand, there is a growing interest in the bacterium's association with cardiovascular, neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 38 publications
2
66
0
3
Order By: Relevance
“…If left untreated, it can cause chronic gastritis, which is associated with various gastrointestinal diseases 2. Various extragastric manifestations of H. pylori have also been reported, including idiopathic thrombocytopenia purpura, vitamin B12 deficiency, and metabolic syndrome 3. Studies have reported H. pylori colonization to be as high as 90% among patients with gastric ulcers or cancer 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…If left untreated, it can cause chronic gastritis, which is associated with various gastrointestinal diseases 2. Various extragastric manifestations of H. pylori have also been reported, including idiopathic thrombocytopenia purpura, vitamin B12 deficiency, and metabolic syndrome 3. Studies have reported H. pylori colonization to be as high as 90% among patients with gastric ulcers or cancer 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cecropins produced by H. pylori inhibit the growth of competing organisms [9], as well as a P-type ATPase, which helps prevent excessive alkalinization of the microenvironment by urease [10]. This last result allowed to hypothesize a role played by H. pylori in other diseases and some evidences has also been pointed out; indeed, this bacterium was shown to survive within monocytes and polymorphonuclear cells, thereby potentially travelling throughout the body [11][12][13].…”
Section: Introductionmentioning
confidence: 95%
“…Whereas H. pylori was initially thought only to cause disease in the upper gut, this microorganism has been implicated in several extra-digestive conditions 6 Recently, infection with H. pylori has emerged as a potential risk factor for type 2 diabetes 7,8 . In some observational studies, H. pylori infection has been associated with glucose intolerance or diabetes, but this has not been a consistent finding 9–20 .…”
Section: Introductionmentioning
confidence: 99%